Accounting for taxation on corporation - a new perspective - Barjoyai Bardai, (Penerbit Universiti Kebangsaan Malaysia, 1982)
The accounting treatment of corporate income taxes on corporation should reflect the system of corporate taxation used in the country. This is to ensure that the accounts would provide the fullest information possible. Advanced corporation tax shows the potential credit to be used for paying dividends. It is a receivable amount to the shareholders. Showing it as an asset in the financial statement will provide better information about the financial position of the corporation. It will however violate the basic principle of seperate legal entity in accounting. It is thought that information about the total amount of available credit should be disclosed in the financial statement, at least in the form of notes to the accounts.